Vertical Conflict, Public Policies, and Pandemic Covid-19: Case Study of Central and Regional Government of DKI Jakarta - Bilal Sukarno; Fathurahman Saleh (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2021)
The Covid-19 pandemic that hit the world, including Indonesia, led all heads of state to respond with various policies aimed at controlling the spread of Covid-19. This research wants to see and analyze the dynamics of central and local government relationships in response to policies taken in handling the Covid-19 pandemic in pre-crisis and crisis through political communication conducted. Using the literature study method, this research concludes that there is no good synergy between the central and local governments in handling Covid-19. A number of policies formulated between the central government and the provincial government of DKI Jakarta, appear to be running on their own without good coordination. Policymaking is seen to highlight sectoral egoism and political communication between actors at the central and local government levels, potentially affecting the political environment in Indonesia which boils down to the influence of electability in the 2024 presidential election. This study recommends the government improve the model of deliberative, mediative, multicultural, consensus, and excellent organizational communication and build a synergistic coordination system, in order to escape sectoral egos and short-term interests that are group and personal. Those political communication models are important especially in disaster management including the Covid-19.